2020
DOI: 10.1007/s10147-020-01666-1
|View full text |Cite
|
Sign up to set email alerts
|

Rationale of combination of anti-PD-1/PD-L1 antibody therapy and radiotherapy for cancer treatment

Abstract: Significant technological advances in radiotherapy have been made in the past few decades. High-precision radiotherapy has recently become popular and is contributing to improvements in the local control of the irradiated target lesions and the reduction of adverse effects. Accordingly, for long-term survival, the importance of systemic cancer control, including at non-irradiated sites, is growing. Toward this challenge, the treatment methods in which anti-PD-1/PD-L1 antibodies that exert systemic effects by r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
105
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 134 publications
(117 citation statements)
references
References 94 publications
3
105
1
1
Order By: Relevance
“…Recently, anti-PD-1/PD-L1 antibodies combined with standard chemotherapy or radiation have been intensively conducted in human’s clinical trial because those therapies were reported to enhance the antitumor immune response 38 , 39 . Twenty seven out of 30 cases had received prior therapies including surgery, radiation, systemic chemotherapy, and other immunotherapy before initiation of the present study, and were judged as refractory to those prier therapies when anti-PD-1 antibody therapy started.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, anti-PD-1/PD-L1 antibodies combined with standard chemotherapy or radiation have been intensively conducted in human’s clinical trial because those therapies were reported to enhance the antitumor immune response 38 , 39 . Twenty seven out of 30 cases had received prior therapies including surgery, radiation, systemic chemotherapy, and other immunotherapy before initiation of the present study, and were judged as refractory to those prier therapies when anti-PD-1 antibody therapy started.…”
Section: Discussionmentioning
confidence: 99%
“…These results underline the negative prognostic value of PD-L1 and highlight the importance of lymphocyte-tumor interface. It is known that RT increases the expression of PD-L1 and promotes anti-tumor immunity [93], therefore, it is reasonable to think that, in the era of immunotherapy, the combination of PD-L1 and CD8 expression may have an important predictive response value [94].…”
Section: Tumor Infiltrating Lymphocytes (Tils In Lung Cancer)mentioning
confidence: 99%
“…The interaction and communication between radioresistance and TME of cancer cells is complicated [26,27]. Basically, the instinct radioresistant property protects cancer cell form death, thus generating less dsDNA and weakening antigen presentation upon radiation [28].…”
Section: Discussionmentioning
confidence: 99%